(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the study of issues of Eastern and Western philosophies of education and the role of their mutual influence on intercultural dialogue based on the study of scientific works of scientists and philosophical literature, as well as the author’s experience in the system of higher education. Appeal to the problem of intercultural dialogue in the philosophy of education is actualized by the fact that in the modern world there is a contradiction between the Western technogenic civilization and the Eastern traditional culture. Also, special attention is paid to such aspects of Eastern and Western philosophy of education as advantages, common features and differences between them, the relationship of the collective and the individual.